Efforts to improve village cleanliness in preventing Covid-19 in Pilobuhuta Village, Batudaa District - Anwar, Herson; Otaya, Lian; Babay, Regianti; laubaha, wiya; Yusuf, Sri Agustin (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
This service activity examines "Efforts to Improve Village Cleanliness in the Prevention of COVID-19 in Pilobuhuta Village, Batudaa District. This research focuses on  the community by cleaning up garbage on the highway and around people's homes. Thus, the existence of KKS-DR student IAIN Sultan Amai Gorontalo who was placed in the village to provide moral and physical assistance in Pilobuhuta Village with the theme of improving village cleanliness in preventing covid19. The activities carried out by KKS-DR Students in Pilobuhuta village are making trash cans from bamboo and hamlet barriers. Community service activities carried out for 45 days by KKS-DR Student IAIN Sultan Amai Gorontalo, are very helpful for the community in carrying out activities every day, especially as students who have the duty to run and devote themselves to the community. In the implementation of this service activity, researchers carry out three stages, namely; Planning Stage, Organizing Stage, and Action Stage. The impact of this service activity is very positive for the community because it gives birth to socio-economic, socio-hygenic, and psycho-social impacts.